Impacts of an egg intervention on nutrient adequacy among young Malawian children. Issue 3 (11th May 2021) - Caswell, Bess L.; Arnold, Charles D.; Lutter, Chessa K.; Iannotti, Lora L.; Chipatala, Raphael; Werner, Elizabeth Rochelle; Maleta, Kenneth M.; Stewart, Christine P.
Abstract: Eggs are a rich source of multiple nutrients that support child growth and development. Provision of eggs as a complementary food may improve dietary adequacy among young children at risk for undernutrition. Our objective was to test the impact of an egg intervention on the adequacy of total nutrient intakes and micronutrient density among 6‐ to 15‐month‐old Malawian children. Children 6 to 9 months old, living in Mangochi District, Malawi, were randomly assigned to the intervention group ( n = 331) receiving an egg per day or a control group ( n = 329) consuming their usual diet. Dietary intakes of macronutrients, vitamins and minerals were assessed using 24‐h recalls at baseline, 3‐month midline and 6‐month endline, with repeat recalls in a subsample. Usual nutrient intake and micronutrient density distributions were modelled to estimate group means and prevalence of inadequacy. Group differences at midline and endline were tested using unequal variance t tests with bootstrapped standard errors. The egg intervention resulted in higher intakes of fat and protein and lower intakes of carbohydrates. The egg group had lower prevalence of inadequacy for selenium, vitamin A, riboflavin, vitamin B5, vitamin B12 and choline. Micronutrient density inadequacy was lower in the egg group for vitamin A and choline at midline and endline, riboflavin at midline and vitamin B5 at endline. Inadequacy of nutrient intakes or density remained highly prevalent in both groups for multiple micronutrients. Though the egg intervention increased intakes of protein and several micronutrients, total intakes and micronutrient density of multiple micronutrients remained far below recommendations.